2022
DOI: 10.1177/20414196211062923
|View full text |Cite
|
Sign up to set email alerts
|

Time of arrival as a diagnostic for far-field high explosive blast waves

Abstract: The ability to accurately determine blast loading parameters will enable more fundamental studies on the sources of blast parameter variability and their influence on the magnitude and form of the loading itself. This will ultimately lead to a better fundamental understanding of blast wave behaviour, and will result in more efficient and effective protective systems and enhanced resilience of critical infrastructure. This article presents a study on time of arrival as a diagnostic for far-field high explosive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…To decide if such reflections needed to be included within the impulse calculation, a custom script was written in MatLab to automatically process the signals. Typically, conventional methods involve the use of concepts such as first maximum in the cumulative impulse (Farrimond et al, 2022), or the use of a curve-fit to determine impulse (Rigby et al, 2014b). Due to the diverse nature of reflection patterns at each sensor location, the cumulative impulse signal can be influenced by these reflections.…”
Section: Discussionmentioning
confidence: 99%
“…To decide if such reflections needed to be included within the impulse calculation, a custom script was written in MatLab to automatically process the signals. Typically, conventional methods involve the use of concepts such as first maximum in the cumulative impulse (Farrimond et al, 2022), or the use of a curve-fit to determine impulse (Rigby et al, 2014b). Due to the diverse nature of reflection patterns at each sensor location, the cumulative impulse signal can be influenced by these reflections.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of this article have identified a consistent feature across all the reflected data collected, which has been discussed in detail as 'sensor ringing' (Rigby et al, 2014a;Farrimond et al, 2022). This, however, is not generally predicted in simplistic numerical models, as seen in Figure 11 which shows the experimentally recorded reflected pressure and specific impulse, compared against APOLLO simulations (with EOS parameters derived from Cheetah and EXPLO5 thermochemical codes, respectively) for 250 g PE10 hemisphere at 2 m stand-off.…”
Section: Numerical Analysis Comparisonmentioning
confidence: 94%
“…Data was recorded using piezo-resistive pressure gauges in the historic tests and current tests and were processed using the automated techniques described in Farrimond et al (2022). Figure 3 shows the configuration of the far-field arena trials.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations